Researcher and Revolutionary : Nikolai Matveevich Kizhner (1867-1935) - Suntsov, Vladislav (My University, 2013)
Nikolai Matveevich Kizhner (1867-1935) was a Russian organic chemist who name is permanently associated with the reaction that he discovered: the Wolff-Kishner reduction of carbonyl compounds. The purpose of this study was to provide a brief synopis of the career of this Russian organic chemist.
Color poster with text, photographs, images, maps, and diagrams.
Keywords: Kizhner, Nikolai Matveevich, 1867-1935; Wolff-Kishner reduction; Organic chemistry; Posters